2022
DOI: 10.1186/s12967-022-03609-y
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in the probiotics as live biotherapeutic products (LBPs) as modulators of gut brain axis related neurological conditions

Abstract: Probiotics have been defined as “living microorganisms that create health benefits in the host when taken in sufficient amounts. Recent developments in the understanding of the relationship between the microbiom and its host have shown evidence about the promising potential of probiotics to improve certain health problems. However, today, there are some confusions about traditional and new generation foods containing probiotics, naming and classifications of them in scientific studies and also their marketing.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 161 publications
(192 reference statements)
0
9
0
Order By: Relevance
“…The pathway that we describe here represents a common etiology that arises from a changed diet and leads to the metabolic inflammation that is present in most cases of the disease. Changes to the gut microbiota and activation of the immune system are involved in many other diseases as well, including neurological disorders (reviewed in [81][82][83] ). It is important to develop a deeper understanding of the interactions between these important aspects of physiology to develop better treatments for a wide range of diseases in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The pathway that we describe here represents a common etiology that arises from a changed diet and leads to the metabolic inflammation that is present in most cases of the disease. Changes to the gut microbiota and activation of the immune system are involved in many other diseases as well, including neurological disorders (reviewed in [81][82][83] ). It is important to develop a deeper understanding of the interactions between these important aspects of physiology to develop better treatments for a wide range of diseases in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, bacteria are the most extensively studied [1]. Growing number of studies demonstrated that intestinal microbiota composition deeply affects human health [2,3]. Regarding cancer, while certain detrimental bacterial species may induce cellular transformation triggering both local and systemic inflammation, other ones protect the host against tumor development, for example by improving the immune system functionality [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…They are “friendly” or “healthy” bacteria that we ingest through foods, beverages, and dietary supplements. Two of the most frequently reported benefits of probiotics are the anti-inflammatory effect that they exert on the central nervous system (CNS) through the gut–brain axis [ 16 , 17 ] and the correction of gut microbiota dysbiosis, which is related to CNS disorders, with poorly understood etiology, and infections [ 18 ].…”
Section: Introductionmentioning
confidence: 99%